Tenure Impacts on Livelihood, Income, Forest Condition, and Equity of an Upland Community in Negros Occidental, Philippines - Nacionales, Nicole; Gevaña, Dixon (Forest and Society, 2021)
This study examined the perceived impacts of the Integrated Social Forestry Program (ISFP) on the biophysical and socio-economic conditions of farmers in Barangay Patag, Silay City, Negros Occidental, Philippines. Specifically, it aimed to: (a) assess the perceived impacts of ISFP on local livelihood, income, forest condition, and equity (LIFE); and (b) identify the factors that are associated with perceived equity; and (c) determine the relationships between perceived equity and ISFP goals. Data were gathered through surveys and a focused group discussion. A total of 41 respondents composed the survey, while six key informants comprised the focused discussion group. Key findings showed that ISFP was perceived to have considerable beneficial impacts on livelihood and income sources. It also had positive impacts on forest condition particularly in the perceived increased of forest cover. Some beneficial impacts were likewise noted for equity across dimensions: gender; education; economic status; and membership. Finally, challenges in sustaining the program underscored the need for strategies to further enhance its positive impacts on the local community’s socio-ecological conditions